2015
DOI: 10.1002/ajmg.a.37069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of facial phenotypes of children with congenital hypopituitarism and their parents: A matched case‐control study

Abstract: Congenital Hypopituitarism (CH) has traditionally been associated with specific facial phenotypes subsumed under the term midface retrusion, based on cephalometric studies. In this study, we used a systematic anthropometric approach to facial morphology in 37 individuals with CH and their parents, primarily of French Canadian ancestry, and compared them to a control group of 78 French Canadian patients with well-controlled type 1 diabetes and their parents. We were able to demonstrate clear morphological diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…On the contrary, in our second patient CI was 30, but pituitary morphology was more severely affected than in the first patient whose CI was 45. Another study performed on patients of French-Canadian ancestry with combined pituitary hormone deficiencies showed that subjects and their parents had midface retrusion, shorter skull base width, underdevelopment of the mandible, and reduced inner canthal distance (36). Hypotelorism may also be a feature of the holoprosencephaly spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in our second patient CI was 30, but pituitary morphology was more severely affected than in the first patient whose CI was 45. Another study performed on patients of French-Canadian ancestry with combined pituitary hormone deficiencies showed that subjects and their parents had midface retrusion, shorter skull base width, underdevelopment of the mandible, and reduced inner canthal distance (36). Hypotelorism may also be a feature of the holoprosencephaly spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that they can be trained to be highly robust for imaging variation, reducing the need for highly controlled subject poses (Xiangyu Zhu et al, 2015). There are a number of current research and commercial efforts to create fully automated analysis pipelines for clinical interpretation of dysmorphologies (Ansari et al, 2014; Ferry et al, 2014; Manousaki et al, 2015; Basel-Vanagaite et al, 2016; Gripp et al, 2016; Baynam et al, 2017; Bengani et al, 2017; Dudding-Byth et al, 2017; Deciphering Developmental Disorders Study, 2017; Gardner et al, 2017; Hadj-Rabia et al, 2017; Kruszka et al, 2017a; Kruszka et al, 2017b; Kruszka et al, 2017c; Lumaka et al, 2017; Shukla et al, 2017; Valentine et al, 2017; Reijnders et al, 2018b; Gurovich et al, 2018; Knaus et al, 2018; Kruszka et al, 2018; Liehr et al, 2018; Pantel et al, 2018; Reijnders et al, 2018a; Reijnders et al, 2018b; Zarate et al, 2018). However, all these efforts are meeting the same barriers to progression of the methods and prospects for clinical impact, challenges to do with data access, ethics, governance, and security.…”
Section: Phenotyping From Photographsmentioning
confidence: 99%
“…[1,2,4,[6][7][8]. Вовторых, и это не менее значимо, не вызывает сомнения доказанный факт наличия клинико-антропологических параллелей, заключающихся в предрасположенности людей того или иного соматического (конституционального) типа к возникновению и развитию ряда нозологических форм, в зависимости эффективности профилактики и лечения их от конституционального типа человека [8,9,12]. Тем самым создается возможность определения антропометрических маркеров, свидетельствующих о повышенном риске развития заболевания, что может обеспечить адекватное формирование групп первичной профилактики, имея в результате не только медицинское, но медико-социальное значения, способствуя оптимизации качества жизни и созданию здоровьесберегающих технологий.…”
Section: Introductionunclassified